Probiotic properties of green banana biomass on health (Research, Society and Development, 2022)
Introduction: The banana (Musa sp.) belonging to the Musa-ceae family, is the most known and consumed tropical fruit in the world. In addition to being affordable, bananas also have a wide variety of nutrients, and are characterized by being easy to prepare and handle. General objective: to present the benefits and effectiveness of green banana biomass and its probiotic functions, acting as a prebiotic and functional food for human health, and an important ally for resistance and increased immunity of the intestinal microbiota. Methodology: This work is an integrative literature review, indexed in the following databases: Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (Lilacs) and Medical Literature Analysis and Retrievel System Online. (MedLine). Results and Discussion: Biomasses are also a source of soluble and insoluble dietary fiber and oligosaccharides, which have functional properties in the digestive system, such as improving intestinal mobility, aiding digestion, and delaying gastric emptying, decreasing blood cholesterol. Conclusion: It is concluded that BBV and its resistant starch is a functional food, acting in the promotion of human and intestinal health as a probiotic food.